2016
DOI: 10.1002/admt.201600102
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Stabilized Blue Phase Liquid Crystals for Photonic Applications

Abstract: Polymer‐stabilized blue phase liquid crystal (PS‐BPLC) is emerging as a promising candidate for next‐generation photonic applications due to its attractive features: nano‐scale structure that enables sub‐millisecond response time, self‐assembly that eliminates the need for surface alignment, and three‐dimensional cubic structure so that it is quasi‐isotropic without applied field. Here, we will look into the photonic properties of PS‐BPLC microscopically and macroscopically, and will focus on the non‐display p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 178 publications
0
21
0
2
Order By: Relevance
“…Wu and co‐workers, in their work on cubic blue phases, had reported that the average twisting power of double‐twisted cylinders results in optical activity which will lead to the accumulation of a small optical rotatory power as linearly polarized light traverses a blue phase sample. In other words, the linearly polarized light will be converted to quasi‐linear (elliptical) polarization and its long axis will be rotated by a small angle, causing light leakage through orthogonal polarizers . Chien and co‐workers realized that they could exploit this behavior to their advantage and that blue phase III could be conveniently distinguished from the isotropic phase due to its optical activity which renders different colors (yellowish‐brown and grayish‐blue) when the analyzer of a polarizing optical microscope (POM) is rotated slightly (2°–4°) to the left or right, that is, when the value of the deviation angle ϕ is positive or negative ( Figure a).…”
Section: The Structure Of the Blue Fog: Solving A 130‐years‐old Puzzlementioning
confidence: 99%
“…Wu and co‐workers, in their work on cubic blue phases, had reported that the average twisting power of double‐twisted cylinders results in optical activity which will lead to the accumulation of a small optical rotatory power as linearly polarized light traverses a blue phase sample. In other words, the linearly polarized light will be converted to quasi‐linear (elliptical) polarization and its long axis will be rotated by a small angle, causing light leakage through orthogonal polarizers . Chien and co‐workers realized that they could exploit this behavior to their advantage and that blue phase III could be conveniently distinguished from the isotropic phase due to its optical activity which renders different colors (yellowish‐brown and grayish‐blue) when the analyzer of a polarizing optical microscope (POM) is rotated slightly (2°–4°) to the left or right, that is, when the value of the deviation angle ϕ is positive or negative ( Figure a).…”
Section: The Structure Of the Blue Fog: Solving A 130‐years‐old Puzzlementioning
confidence: 99%
“…Blue phase liquid crystals (BPLCs) have recently become promising candidates for photonic applications [9][10][11][12][13][14][15][16][17][18][19]. BPLC lenses have been displayed experimentally with a fast response time [20], simple fabrication process [21], and the polarization-independent property [22,23]. To overcome the polarization dependence of conventional LC lens, polymer-stabilized blue-phase liquid crystals (PSBPLCs) and the Kerr effect have been considered as the better candidates [10,24].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a LC lens, various devices such as a multi-strip or hole-patterned electrode [8,[14][15][16][17], LC lens with switchable positive and negative focal lengths [18], optically hidden dielectric structure [19,20], and polymer-stabilized blue phase LC [21][22][23][24][25] have been studied in recent years. Among these attempts, the multi-strip electrode structure could generate a spherical phase profile, but the driving mode is very complicated by individually addressing the pixelated electrodes.…”
Section: Introductionmentioning
confidence: 99%